2022
DOI: 10.21142/2523-2754-1001-2022-096
|View full text |Cite
|
Sign up to set email alerts
|

Pronóstico de caninos impactados según su posición en el maxilar superior mediante diferentes análisis radiográficos

Abstract: Introducción: La impactación de los caninos es una anomalía en la que el diente se halla impedido para erupcionar. Se da cuando la erupción ha demorado y existe evidencia radiográfica. Objetivo: Determinar el pronóstico de caninos impactados según su posición en el maxilar mediante diferentes análisis: Ericson & Kurol, Warford y Power & Short; en pacientes que acuden a consultorios privados en la ciudad de Asunción de los años 2015 al 2020. Metodología: El diseño es observacional descriptivo de corte t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
1
0
3
Order By: Relevance
“…Another challenge was periodontal health, which can be affected by various factors, such as the type of surgical procedure selected to expose the crown of the impacted tooth, the eruption of the teeth through the attached gingiva or mucosa, the hygiene methods used, and the anatomical characteristics of the mandibular bone, including reduced bicortical width and alveolar rigidity [ 39 ]. It has been shown that surgical procedures closed by the buccal approach, such as that used in this case report, offer better results [ 40 44 ]. Nevertheless, coronal elongation of the canines was observed in the patient, with cervical exposure and possible projection of the roots through the attached gingiva margin due to the narrowness of the alveolar bone corridor, for which it was recommended to keep the canine and anteroinferior area in optimal hygiene conditions and monitor the stability of the occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Another challenge was periodontal health, which can be affected by various factors, such as the type of surgical procedure selected to expose the crown of the impacted tooth, the eruption of the teeth through the attached gingiva or mucosa, the hygiene methods used, and the anatomical characteristics of the mandibular bone, including reduced bicortical width and alveolar rigidity [ 39 ]. It has been shown that surgical procedures closed by the buccal approach, such as that used in this case report, offer better results [ 40 44 ]. Nevertheless, coronal elongation of the canines was observed in the patient, with cervical exposure and possible projection of the roots through the attached gingiva margin due to the narrowness of the alveolar bone corridor, for which it was recommended to keep the canine and anteroinferior area in optimal hygiene conditions and monitor the stability of the occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…• Desplazamiento de las piezas dentarias • Disminución de la longitud del arco dental (Diaz-Reissner et al, 2022) Los caninos desempeñan un papel importante cuando tienen un buen posicionamiento y hay una adecuada alineación, se observa una línea de sonrisa estética y oclusión aceptable. (Hamada et al, 2019) Es importante la detección temprana de caninos impactados, principalmente cuando la pérdida prematura de los caninos deciduos origina la falta de espacio para la erupción normal de los caninos permanentes; por tanto, el examen por imágenes resulta fundamental para diagnosticar y plantear el tratamiento oportuno según el pronóstico del caso.…”
Section: Los Factores Sistémicos Asociados a Los Dientes Impactados Sonunclassified
“…Se encontró que la presencia de caninos superiores impactados fue más frecuente en mujeres, con ubicación unilateral y posición palatina. (Diaz-Reissner et al, 2022) En cuanto al pronóstico para que este sea propicio, hay una serie de factores que lo imposibilitan como es la edad y la cooperación del paciente, la salud general y dental, el apiñamiento o espacio dental. (Hsu et al, 2020) Hay dos teorías principales con respecto a los caninos maxilares desplazados hacia el paladar son:…”
Section: Los Factores Sistémicos Asociados a Los Dientes Impactados Sonunclassified
See 1 more Smart Citation